Neuroprotective Effects of Eupatorin against Valproic Acid-Induced Autism-Like Phenotypes in Zebrafish Embryos - Farasani, Abdullah (Indian Journal of Pharmaceutical Education and Research)
Purpose: Autism Spectrum Disorder (ASD) is a neurodevelopmental condition often linked to oxidative stress and dysregulated apoptosis. Valproic Acid (VPA), a known teratogen, induces ASD-like behavioral and morphological abnormalities in zebrafish larvae. This study evaluated the neuroprotective potential of eupatorin, a naturally occurring methoxylated flavone, against VPA-induced developmental and neurobehavioral toxicity in zebrafish embryos. Materials and Methods: In this study, zebrafish embryos at 4 hpf were exposed to VPA (5 and 10 μg/mL) with or without eupatorin (5 nM) co-treatment until 96 hpf. Survival, heart rate, and morphology were examined microscopically; locomotor and social behaviors were assessed using automated tracking; oxidative stress biomarkers (ROS, H2O2, SOD) were quantified fluorometrically; and apoptotic cells were detected using acridine orange staining. Results: Embryos were exposed to VPA (5 and 10 μg/mL) with or without eupatorin (5 nM) co-treatment from 4 to 96 Hours Post-Fertilization (hpf). Eupatorin co-treatment significantly improved the survival rate, regularized the heart rate towards the control level, and reduced morphological defects such as pericardial edema and tail malformations. Behavioral assays revealed that eupatorin mitigated VPA-induced hyperactivity, social deficits, and stereotyped swimming behavior. Additionally, eupatorin restored redox homeostasis by lowering ROS and H2O2 levels while enhancing Superoxide Dismutase (SOD) activity. Acridine Orange (AO) staining confirmed reduced apoptotic cell death, particularly in the brain region. Conclusion: Collectively, these findings suggest that eupatorin alleviates oxidative stress-mediated neurodevelopmental impairments and may serve as a promising candidate for ASD intervention.
Keywords: Apoptosis; Behavioral phenotype; Developmental neurotoxicity; Neuroprotection; Oxidative stress; ROS